SISTEM PENINGKATAN PRODUKTIVITAS MESIN PRODUKSI ASAM SULFAT DENGAN METODA TOTAL PRODUCTIVE MAINTENANCE - Tri Sutrisno (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2015)
Sulfuric acid production is a continuous process. With the process running constantly then the conditionof machinery should be maintained properly so as not frequent downtime. Downtime will result indecreased production achievement and damage the quality of the product.To overcome this designed a treatment system using the concept of TPM in a corporateenvironment, which is expected to bring harmony between the operator as to the implementation of theproduction engineer and production planner’s parties as well as the maintenance. The concept of totalproductive maintenance is one way for the company's improved performance is more stable. Theconcept of total productive maintenance consists of three important components of a total approach,efforts productive, and maintenance. Of the three components can be explained using the concept ofOverall Equipment Effectiveness and autonomous maintenance.